2018
DOI: 10.1039/c8an00216a
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific characterization and quantitation ofN-glycopeptides in PKM2 knockout breast cancer cells using DiLeu isobaric tags enabled by electron-transfer/higher-energy collision dissociation (EThcD)

Abstract: The system-wide site-specific analysis of intact glycopeptides is crucial for understanding the exact functional relevance of protein glycosylation. A dedicated workflow with the capability to simultaneously characterize and quantify intact glycopeptides in a site-specific and high-throughput manner is essential to reveal specific glycosylation alteration patterns in complex biological systems. In this study, an enhanced, dedicated, large-scale site-specific quantitative N-glycoproteomics workflow has been est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 80 publications
1
63
0
Order By: Relevance
“…However, the ability to analyze the glycopeptides has remained a challenge. In recent work, there have been a number of techniques developed to deal with this problem (Table ), including collision‐induced dissociation (CID)/electron‐transfer dissociation (ETD) (Alley et al, ), CID/higher‐energy collisional dissociation (HCD) (Segu & Mechref, ; Lee et al, ), stepped HCD (Liu et al, ; Yin et al, ), and electron‐transfer/higher‐energy collision dissociation (EThcD) (Yu et al, ; Chen et al, ; Glover et al, ), for example. The use of CID/ETD MS to analyze glycopeptides has been recently reviewed by Mechref (Mechref, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the ability to analyze the glycopeptides has remained a challenge. In recent work, there have been a number of techniques developed to deal with this problem (Table ), including collision‐induced dissociation (CID)/electron‐transfer dissociation (ETD) (Alley et al, ), CID/higher‐energy collisional dissociation (HCD) (Segu & Mechref, ; Lee et al, ), stepped HCD (Liu et al, ; Yin et al, ), and electron‐transfer/higher‐energy collision dissociation (EThcD) (Yu et al, ; Chen et al, ; Glover et al, ), for example. The use of CID/ETD MS to analyze glycopeptides has been recently reviewed by Mechref (Mechref, ).…”
Section: Methodsmentioning
confidence: 99%
“…At least two ratios need to be observed among the three technical replicates. For the intact N-glycopeptides quantitated at least twice, the p value was calculated using t-test [19]; and the intact N-glycopeptides with a fold change of no less than 1.5 and p value no bigger than 0.05 were classified as differentially expressed intact N-glycopeptides.…”
Section: Relative Quantitation Of Differentially Expressed Intact N-gmentioning
confidence: 99%
“…Recent glycomics and glycoproteomics‐centric studies have demonstrated that PMPs are also elevated glycosylation signatures associated with various human cancers including those of ovarian (Everest‐Dass et al ., ; Chen et al ., ), colorectal (Joosten et al ., ; Balog et al ., ; Sethi et al ., ; Kaprio et al ., ; Holst et al ., ), breast (Lee et al ., ; Chen et al ., ), lung (Hua et al ., ; Ruhaak et al ., ; Wang et al ., ), paraganglioma (Leijon et al ., ), glioblastoma multiforme (Becker et al ., ), skin (Moginger et al ., ) and prostate (Shah et al ., ) origin. By systematically interrogating a very large collection of nearly 500 N ‐glycomics LC‐MS/MS data sets obtained from 11 cancer types and subtypes, we have obtained solid evidence that PMGs are significant features of human cancers and, at least in part, expressed on cancer cell surfaces (S. Chatterjee, L. Y. Lee, R. Kawahara, J. L. Abrahams, B. Adamczyk, M. Anugraham, C. Ashwood, Z. Sumer‐Bayraktar, M. T. Briggs, J. H. L. Chik, A. Everest‐Dass, S. Förster, H. Hinneburg, K. R. M. Leite, I. Loke, U. Möginger, E. S. X. Moh, M. Nakano, S. Recuero, M. K. Sethi, M. Srougi, K. Stavenhagen, V. Venkatakrishnan, K. Wongtrakul‐Kish, S. Diestel, P. Hoffmann, N. G. Karlsson, D. Kolarich, M. P. Molloy, M. H. Muders, M. K. Oehler, N. H. Packer, G. Palmisano & M. Thaysen‐Andersen, in preparation).…”
Section: Human Pmps: Cues From Higher and Lower Eukaryotesmentioning
confidence: 99%